2010
DOI: 10.1038/gt.2010.134
|View full text |Cite
|
Sign up to set email alerts
|

Minimal doses of a sequence-optimized transgene mediate high-level and long-term EPO expression in vivo: challenging CpG-free gene design

Abstract: Advanced gene delivery techniques can be combined with rational gene design to further improve the efficiency of plasmid DNA (pDNA)-mediated transgene expression in vivo. Herein, we analyzed the influence of intragenic sequence modifications on transgene expression in vitro and in vivo using murine erythropoietin (mEPO) as a transgene model. A single electro-gene transfer of an RNA-and codon-optimized mEPOopt gene into skeletal muscle resulted in a 3-to 4-fold increase of mEPO production sustained for 41 year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
16
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 59 publications
3
16
0
1
Order By: Relevance
“…Our results are very encouraging, since high expressers with an expression level increase of 2.6-fold to 15-fold showed no detrimental effect on solubility (JNK1, JNK3, p38a) or function (JNK1, JNK3 and CDC2). This positive effect of gene optimization on protein expression resulting in functional protein was also demonstrated in a recent publication by some of the authors [50], where a single electro-gene transfer of an RNA- and codon optimized EPO gene into skeletal muscle resulted in a 3- to 4-fold increase of EPO production over mice treated with non-optimized EPO genes, sustaining for >1 year and triggering a significant increase in hematocrit and hemoglobin without causing adverse effects [50]. Furthermore in addition to the mechanistic insights of overexpression in the stable system described for MIP1-α, the study provides supporting mechanistic insights of overexpression in a transient system [50].…”
Section: Discussionsupporting
confidence: 67%
“…Our results are very encouraging, since high expressers with an expression level increase of 2.6-fold to 15-fold showed no detrimental effect on solubility (JNK1, JNK3, p38a) or function (JNK1, JNK3 and CDC2). This positive effect of gene optimization on protein expression resulting in functional protein was also demonstrated in a recent publication by some of the authors [50], where a single electro-gene transfer of an RNA- and codon optimized EPO gene into skeletal muscle resulted in a 3- to 4-fold increase of EPO production over mice treated with non-optimized EPO genes, sustaining for >1 year and triggering a significant increase in hematocrit and hemoglobin without causing adverse effects [50]. Furthermore in addition to the mechanistic insights of overexpression in the stable system described for MIP1-α, the study provides supporting mechanistic insights of overexpression in a transient system [50].…”
Section: Discussionsupporting
confidence: 67%
“…Several studies have reported that removal of CG dinucleotides from pDNA can achieve long-term transgene expression by avoiding the inflammatory response (Kosovac et al, 2011;Pringle et al, 2012). Therefore, we confirmed the duration of transgene expression of a CpG free plasmid encoding a secreted luciferase protein, Lucia, at the serum level.…”
Section: Discussionsupporting
confidence: 65%
“…The latter can be due to various effects, such as increasing mRNA stability 58 or increasing de novo mRNA synthesis of transgenes. 19,25 For hgfp genes with modified CpG content in the open reading frame, we have previously shown, using T7 polymerase-driven transcription in the cytoplasm of mammalian cells, that modulation of the CpG content does not affect mRNA stability or translational efficiency. 18 To avoid the spreading of repressive epigenetic marks surrounding the integration locus into the proximal transgene and to prevent loss of the transgene through the outgrowth of transgene-lacking cells, transgene expression is optimally conducted under selection pressure.…”
Section: Discussionmentioning
confidence: 99%
“…14,[22][23][24] In contrast, it was shown that CpG dinucleotides in the transgene open reading frame can provide improved and long-term transgene expression in mouse tissue. 25 These conflicting observations are suggested to be due to the use of different promoters and transgenes, which vary in codon quality or CpG content, and are flanked by diverse noncoding regions or cis-acting sequence elements. Moreover, different delivery systems were used in these studies, resulting in an episomal state or the random integration of multiple gene copies into the host cell genome.…”
mentioning
confidence: 98%